“Nasi Sawo” as a Legitimacy of The Rejang Tribe Community's Traditional Marriage in The Urf Perspective - Suwarjin Suwarjin (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2020)
This study examines the tradition of "Nasi Sawo," which signifies the legality of traditional marriages in the Rejang tribal community, Bengkulu. At first glance, there is a discrepancy between the rules of Islamic law and customary practices regarding the validity of marriage. Researchers used a qualitative-field research method with a normative-sociological approach. His study of Islamic law uses the theory of Urf. This study found that philosophically "Nasi Sawo" means hope for harmony and family benefits. The obligation to carry out this tradition is a sign of the validity of marriage according to custom. However, according to Islamic law, it is still valid if it fulfills the conditions and pillars. This tradition is practiced because, previously, no marriage registration was used as a sign of the validity of marriage legally. The Nasi Sawo tradition is included in the urf sahih category because of its good values and the obligation to implement it, which is not considered a sign of the legality of marriage from an Islamic legal standpoint but from a customary perspective. Penelitian ini mengkaji tradisi "nasi sawo" yang digunakan sebagai tanda legalitas pernikahan adat masyarakat suku rejang, Bengkulu. secara sekilas, terdapat ketidaksesuaian antara aturan hukum Islam dengan aturan adat tentang keabsahan pernikahan. Peneliti menggunakan metode penelitian kualitatif-lapangan dengan pendekatan normatif-sosiologis. kajian hukum Islamnya menggunakan teori Urf. penelitian ini menemukan bahwa secara filosofis "Nasi Sawo" memiliki makna harapan akan kerhamonisan dan kebermanfaatan keluarga dalam kehidupan. kewajiban melaksanakan tradisi ini adalah sebagai tanda keabsahan perkawinan secara adatnya, namun secara hukum Islam tetap sah jika sudah memenuhi syarat dan rukunnya. Tradisi ini dipraktekkan karena dulunya belum ada pencatatan nikah yang digunakan sebagai tanda keabsahan nikah secara hukum. tradisi Nasi Sawo termasuk dalam kategori urf shahih, karena nilai-nilai baik yang terkandung di dalamnya dan kewajiban pelaksanaannya yang tidak dianggap sebagai tanda legalitas pernikahan dalam sisi hukum islamnya, namun dalam sisi adatnya